2014
DOI: 10.1007/jhep01(2014)153
|View full text |Cite
|
Sign up to set email alerts
|

Hairy planar black holes in higher dimensions

Abstract: We construct exact hairy planar black holes in D-dimensional AdS gravity. These solutions are regular except at the singularity and have stress-energy that satisfies the null energy condition. We present a detailed analysis of their thermodynamical properties and show that the first law is satisfied. We also discuss these solutions in the context of AdS/CFT duality and construct the associated c-function.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 47 publications
(83 reference statements)
0
73
0
Order By: Relevance
“…It should be noted that the boundary conditions φ 2 (φ 1 ) of our scalar field Ansatzes given by (17) preserve all the asymptotic AdS symmetries. The analysis of [5,6,34] showed that, under such special boundary conditions, the masses calculated by Wald's formula [32,33], the Hamiltonian formula [27,30] and the AMD [35,36] conformal method are the same.…”
Section: B the Thermodynamicsmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that the boundary conditions φ 2 (φ 1 ) of our scalar field Ansatzes given by (17) preserve all the asymptotic AdS symmetries. The analysis of [5,6,34] showed that, under such special boundary conditions, the masses calculated by Wald's formula [32,33], the Hamiltonian formula [27,30] and the AMD [35,36] conformal method are the same.…”
Section: B the Thermodynamicsmentioning
confidence: 99%
“…However, as there is too much freedom in constructing a scalar potential without breaking any essential symmetry, starting from some arbitrary scalar potential, the possibility to find an exact solution could be almost null. Hence it is not surprising that there is not much progress [9,10] in constructing exact solutions for a long time until recently [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], people begin to think in a reverse way, which is trying to give a proper Ansatz for the scalar field first then deriving the corresponding Lagrangian (or scalar potential) through the EOMs at last.…”
Section: Arxiv:150102829v3 [Hep-th] 6 Nov 2015mentioning
confidence: 99%
See 3 more Smart Citations